The Use of a Case Study Approach to Recruit High School Students with an Interest in Healthcare to Medical Laboratory Sciences and other Allied Health Professions...American Society for Clinical Laboratory Science (ASCLS) Clinical Laboratory Educators’ Conference (CLEC), February 25-27, 2016 in Minneapolis, Minnesota. - Landis-Piwowar, Kristin (Clinical Laboratory Science)
Medical Laboratory Science educators continually strive to adopt effective techniques that yield both improved understanding of and tools to recruit students to the profession. Macomb Community College, in partnership with Oakland University, offers a four-day summer camp entitled, "Healthcare Professions Camp," in which high school students explore health related professions. The Oakland University, Biomedical Diagnostic and Therapeutic Sciences Program (BDTS) offers Bachelor of Science degrees in Medical Laboratory Science, Histotechnology, Nuclear Medicine Technology and Radiologic Technology and is thus an important contributor to this event. The BDTS program provides a full day of activity for the camp. The experience is designed to mimic the examination of a single patient who is evaluated in different departments of a hospital and, most notably, different areas of the clinical laboratory. The camp participants are escorted through the "radiology department" where they encounter radiologic technologists and nuclear medicine technologists and to the "clinical pathology department" where they perform procedures in immunohematology, urinalysis, microbiology, and hematology. At the end of the day, the participants compile all of the data that was collected on the patient, assess the significance of their findings, and discuss the importance of the numerous individuals that were involved in the patient's diagnosis. While the case and some of the specimens are not real, the camp participants leave the camp with a new perspective on healthcare professions and note that their experience was positive and impactful.